Unveiling Hidden Market Manifolds : Transformer-Powered TDA with Bayesian Edge - Sheredeko, Oleksandr; Tomanová, Petra; Fičura, Milan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This paper presents a high-frequency trading (HFT) framework designed to exploit short-term market trends. A key concept is the processing approach that employs topological data analysis to exploit volatility regimes. These refined signals are passed into a Bayesian inference model that quantifies uncertainty.
Vedoucí práce: Petra Tomanová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses